A biochar-based medium in the biofiltration system: Removal efficiency, microorganism propagation, and the medium penetration modeling. (2nd July 2016) - Baltrėnas, Pranas; Baltrėnaitė, Edita; Kleiza, Jonas; Švedienė, Jurgita
ABSTRACT: Biofiltration is a method of biological treatment belonging to cleaner technologies because it does not produce secondary air pollutants, but helps to integrate natural processes in microorganisms for decomposing volatile air pollutants and solving odor problems. The birch wood biochar has been chosen as a principal material for biofilter bed medium. The experiments were conducted at the temperatures of 24, 28, and 32 °C, while the concentration of acetone, xylene, and ammonium reached 300 mg/m 3 and the flow rate was 100 m 3 /hr. Before passing through the stage of the experimental research into the packing material inside biofilters, microorganisms were introduced. Four strains of microorganisms (including micromycetes Aspergillus versicolor BF-4 and Cladosporium herbarum 7KA, as well as yeast Exophiala sp. BF1 and bacterium Bacillus subtilis B20) were selected. At the inlet loading rate of 120 g/m 3 /hr, the highest elimination capacity of xylene in the biochar-based biofilter with the inoculated medium was 103 g/m 3 /hr, whereas that of ammonia was 102 g/m 3 /hr and that of acetone was 97 g/m 3 /hr, respectively. The maximum removal efficiency reached 86%, 85%, and 81%, respectively. The temperature condition (though characterized by some rapid changes) can hardly have a considerable influence on the biological effect (i.e., microbiological activity) of biofiltration; however, it can cause the changes in physical properties (e.g., solubility) of the investigated compounds. Implications : The birch biochar can be successfully used in the biofiltration system for propagation of inoculated microorganisms, biodegrading acetone, xylene, and ammonia. At the inlet loading rate of 120 g/m 3 /hr, the highest elimination capacity of xylene was 103 g/m 3 /hr, that of ammonia was 102 g/m 3 /hr, and that of acetone was 97 g/m 3 /hr, respectively. The morphological structure of biochar can be affected by the aggressive air contaminants, causing the change in the medium specific surface area, which is one of the factors controlling the biofilter performance. Although biological effects in biofiltration are typically considered to be more important than physical effects, the former may be more important for compounds with high Henry's Law coefficient values, and the biofilter design should thus provide conditions for better compound absorption.